2010
DOI: 10.1088/0004-637x/714/2/1689
|View full text |Cite
|
Sign up to set email alerts
|

THE DRAO PLANCK DEEP FIELDS: THE POLARIZATION PROPERTIES OF RADIO GALAXIES AT 1.4 GHz

Abstract: We present results of deep polarization imaging at 1.4 GHz with the Dominion Radio Astrophysical Observatory as part of the DRAO Planck Deep Fields project. This deep extragalactic field covers 15.16 deg 2 centered at α 2000 = 16 h 14 m and δ 2000 = 54 • 56 ′ , has an angular resolution of 42 ′′ × 62 ′′ at the field center, and reaches a sensitivity of 55 µJy beam −1 in Stokes I and 45 µJy beam −1 in Stokes Q and U. We detect 958 radio sources in Stokes I of which 136 are detected in polarization. We present t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
107
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(128 citation statements)
references
References 37 publications
20
107
1
Order By: Relevance
“…The anti-correlation between total intensity and fractional polarization at 1.4 GHz has been extensively discussed (such as Mesa et al 2002;Tucci et al 2004;Taylor et al 2007;Grant et al 2010;Subrahmanyan et al 2010;Stil et al 2014). Recently, Banfield et al (2014) used WISE colors to suggest that the anti-correlation was due to the difference in environments between WISE-AGNs (IR colors dominated by AGN) and WISE-Ellipticals (IR colors dominated by starlight).…”
Section: The Origin Of the Total Intensity Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-correlation between total intensity and fractional polarization at 1.4 GHz has been extensively discussed (such as Mesa et al 2002;Tucci et al 2004;Taylor et al 2007;Grant et al 2010;Subrahmanyan et al 2010;Stil et al 2014). Recently, Banfield et al (2014) used WISE colors to suggest that the anti-correlation was due to the difference in environments between WISE-AGNs (IR colors dominated by AGN) and WISE-Ellipticals (IR colors dominated by starlight).…”
Section: The Origin Of the Total Intensity Andmentioning
confidence: 99%
“…When many lines of sight each have independent single Faraday depths, this problem is approached statistically. Another long-standing puzzle is the anti-correlation between the total intensity of radio sources and their degree of polarization, as observed by many groups such as Mesa et al (2002), Tucci et al (2004), Sadler et al (2006), Taylor et al (2007), Grant et al (2010), Subrahmanyan et al (2010), and Stil et al (2014). The physical nature of this relation has been a mystery for almost a decade and is confused by its dependency on other source properties.…”
Section: Introductionmentioning
confidence: 99%
“…Sirothia et al (2009) observed it at 325 MHz using the Giant Metrewave Radio Telescope (GMRT), with the objective of identifying active galactic nuclei and starburst galaxies and examining their evolution with cosmic epoch. Grant et al (2010) observed 15 deg 2 with the Dominion Radio Astrophysical Observatory synthesis telescope at 1420 MHz to a minimum rms of 55 µJy beam −1 in Stokes I and 45 µJy beam −1 in polarisation. Banfield et al (2011) observed 10 deg 2 at 1.4 GHz with the JVLA in B configuration to a minimum rms of 87 µJy beam −1 in total intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, recent polarimetric studies have indicated an increase in the fractional polarization of faint extragalactic radio sources (e.g. Taylor et al ; Grant et al ; Shi et al ; Subrahmanyan et al ), which are difficult to reconcile with population modelling (O'Sullivan et al ). We seek here to subject the process of polarization measurement to close scrutiny, and to provide the community with a measurement tool that has been assessed within a controlled testing environment.…”
Section: Introductionmentioning
confidence: 99%